2018
DOI: 10.1002/jwmg.21570
|View full text |Cite
|
Sign up to set email alerts
|

Association of moose parturition and post‐parturition habitat with calf survival

Abstract: Habitat use during calving and the energetically demanding post‐parturition period can be an important determinant of neonatal survival. The moose (Alces alces) population in northeastern Minnesota, USA declined 65% from 2006 to 2018. During 2013–2015, annual survival of calves was estimated as low as 28%. We remotely monitored global positioning system (GPS)‐collared adult female moose and their neonates during the calving and post‐parturition seasons to examine calving movements, birth‐sites, habitat use, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 52 publications
(91 reference statements)
0
27
1
Order By: Relevance
“…Generally, we observed mortalities to occur once females and their calves departed calving sites, consistent with other studies that reported calves were rarely killed at calving sites (Bubenik ). Previous studies have documented considerable variability in land cover types used by females for calving and during post‐parturition (Leptich and Gilbert , Addison et al , McGraw et al ) but have generally agreed that females tradeoff forage for predator avoidance (Bowyer et al , Testa et al 2000 b , Severud et al ). However, there is risk to either movement or remaining cryptic (Lima and Dill ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, we observed mortalities to occur once females and their calves departed calving sites, consistent with other studies that reported calves were rarely killed at calving sites (Bubenik ). Previous studies have documented considerable variability in land cover types used by females for calving and during post‐parturition (Leptich and Gilbert , Addison et al , McGraw et al ) but have generally agreed that females tradeoff forage for predator avoidance (Bowyer et al , Testa et al 2000 b , Severud et al ). However, there is risk to either movement or remaining cryptic (Lima and Dill ).…”
Section: Discussionmentioning
confidence: 99%
“…Female ungulates select birth sites and habitat for nursery groups (i.e., females with young) based on a variety of trade-offs (Bowyer, 1991;Bowyer, 1991, 1994). These tradeoffs include predation risk, exposure to extreme weather, and forage quality and availability for the mother to fulfill nutritional requirements during late gestation and lactation (Festa-Bianchet, 1988b;Berger, 1991;Severud et al, 2019). For example, female bighorn sheep often return to the same general area each year to give birth (Geist, 1971;Etchberger and Krausman, 1999;Whiting et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, desert bighorn sheep (O. c. nelsoni) give birth in almost any month, ostensibly because of a less predictable growing season (Bunnell, 1982;Thompson and Turner, 1982;Rubin et al, 2000). Delineation of birthing habitat has important implications for the conservation, reproductive biology, and perpetuation of bighorn populations (Etchberger and Krausman, 1999;Wiedmann and Sargeant, 2014;Smith et al, 2015), and is a topic that is receiving increased attention for land-use planning (Severud et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations